Strategi Pengembangan Usaha pada AK Laundry dengan Menggunakan Analisis Swot - Rizkia Umami; Purwati Purwati; Dewi Fadila (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This research aims to formulate a business development strategy for AK Laundry, a micro, small, and medium enterprise (MSME) located in Palembang that operates in the laundry service industry. As competition in this sector continues to intensify, MSMEs are required to adapt quickly through effective strategic planning. The study employed a descriptive qualitative approach, with data collected through interviews, direct observations, documentation, and questionnaires, ensuring a holistic understanding of both internal and external conditions. The analysis was carried out using the SWOT framework, which identifies internal strengths and weaknesses, as well as external opportunities and threats. The findings reveal that AK Laundry possesses several strengths, including good relationships with its loyal customer base, competitive pricing that appeals to a wide range of market segments, and a strategic location that facilitates accessibility. However, weaknesses were also identified, such as limited promotional efforts, particularly in digital channels, and occasional delays in completing customer orders, which may affect satisfaction and trust. From an external perspective, AK Laundry has opportunities to expand its services, particularly through the growing demand for pickup and delivery facilities, as well as changes in consumer lifestyles that increasingly prioritize practicality and efficiency. Nevertheless, the enterprise must also address potential threats, such as intense competition in pricing strategies among similar businesses and the risk of item loss, which could undermine its reputation. Based on the SWOT matrix, AK Laundry is positioned in Quadrant I, indicating that it holds considerable potential for aggressive growth. Therefore, the recommended strategies include strengthening digital marketing initiatives, introducing innovative services to differentiate from competitors, enhancing employee competencies through training programs, and upgrading equipment to improve service quality and speed. These strategies are expected to help AK Laundry leverage its strengths and opportunities effectively, ensuring sustainable development and competitiveness in the MSME laundry service sector.